Human metapneumovirus: insights from a ten-year molecular and epidemiological analysis in Germany. - Janine Reiche (Public Library of Science (PLoS), 2014)
Human metapneumovirus (HMPV) is a cause of respiratory tract illness at all ages. In this study the epidemiological and molecular diversity among patients of different ages was investigated. Between 2000-2001 and 2009-2010, HMPV was detected in 3% (138/4,549) of samples from outpatients with influenza-like illness with a new, sensitive real-time RT-PCR assay. Several hundred (797) clinical specimens from hospitalized children below the age of 4 years with acute respiratory illness were investigated and HMPV was detected in 11.9% of them. Investigation of outpatients revealed that HMPV infections occurred in individuals of all ages but were most prevalent in children (0-4 years) and the elderly (>60 years). The most present clinical features of HMPV infections were cough, bronchitis, fever/shivers and pneumonia. About two thirds of HMPV-positive samples were detected in February and March throughout the study period. Molecular characterization of HMPV revealed a complex cyclic pattern of group dominance where HMPV subgroup A and B viruses predominated in general for three consecutive seasons. German HMPV represented all genetic lineages including A1, A2, B1, B2, sub-clusters A2a and A2b. For Germany, not only time-dependent circulation of lineages and sub-clusters was observed but also co-circulation of two or three predominant lineages. Two newly emerging amino acid substitutions (positions 223 and 280) of lineage B2 were detected in seven German HMPV sequences. Our study gives new insights into the molecular epidemiology of HMPV in in- and outpatients over a time period of 10 years for the first time. It is one of only few long-term surveillance studies in Europe, and allows comparative molecular analyses of HMPV circulating worldwide.